Virtual Droop Control Framework and Stability Analyses for Microgrids with High Penetration of Renewables - (:unkn) unknown (My University, 2015)
Microgrids can provide the most promising means of integrating large amounts of distributed sources into the power grid and can supply reliable power to critical loads. However, managing distributed sources and loads within a microgrid during island and grid-tie modes and during transitions is a challenge. Stable operation of a microgrid is a concern specifically during the starting of motor loads, switching of large loads, and in presence of high penetration of renewable resources. Hence, a generalized control framework is required to regulate microgrid voltage and frequency, maintain power quality, manage Distributed Generations (DG) and ensure microgrid stability. Several control methods have been developed for microgrid control. Majority of these techniques are based on natural droop control or modified natural droop control, which rely on voltage and frequency variations as inputs to control algorithms. At present, there are no methods available for sizing the capacities needed to ensure reliable operation and stability. A new microgrid control framework, Virtual Droop Control (VDC), for power management as well as for voltage and frequency regulation is proposed in this thesis. The proposed control method analyzes the effect of intermittent resources and dispatches the power commands to individual generation assets ensuring stable operation of the microgrid. The proposed method is described, formulated and compared with existing natural droop control technique in this dissertation. The unit commitment algorithm has also been implemented to manage non-renewable sources to improve system efficiency. The proposed technique operates the microgrid at a constant voltage and frequency and uses communications for power sharing. It also provides the means to operate the microgrid in case of lost communication or sabotage on the communication network. The modeling results of the Virtual VDC technique have been compared with exiting microgrid control methods including natural droop control technique. A laboratory setup, that consists of a 100kW natural gas generator, a 56 kWh Li-ion battery with a 250kW inverter, and a 100kW load bank, has been built and tested. The results of the setup have been provided, confirming the viability of the proposed technique. Detailed analysis for intentional islanding, unintentional islanding, and reconnection are presented. The state space model has been developed for the Fort Sill microgrid and the stability analysis has been performed to verify stability of a microgrid in various scenarios. The proposed method has been applied to the Fort Sill microgrid and examined for effectiveness and viability. A modified control technique is also proposed to regulate the voltage and frequency for high penetration of renewable energy, which can be used with VDC framework. This technique allows the improvement of efficiency and power quality indexes for critical loads while reducing greenhouse gas emissions. The standard IEEE 34 bus system is modified and adapted to function as a microgrid test bed. Three different cases were studied and analyzed. The CO2 emission, efficiency, and power quality indexes have been calculated and compared for all three cases in order to verify the performance of the proposed control technique.
Keywords: Microgrid; Power Electronics; Power Management; Power System; Renewable Energy; Virtual Droop Control